2018
DOI: 10.1007/s12272-018-1066-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective effect of eupatilin against indomethacin-induced damage in feline esophageal epithelial cells: relevance of HSP27 and HSP70

Abstract: Indomethacin is a non-steroidal anti-inflammatory drug with clearly known side effects on the gastrointestinal tract. The purpose of the present study was to investigate whether eupatilin inhibit cell injury induced by indomethacin in cultured feline esophageal epithelial cells (EECs). EECs were used to investigate the ability of eupatilin to induce the expression of heat shock proteins (HSP27 and HSP70) and analyze its cytoprotective effect against indomethacin-induced damage. The treatment of EECs with indom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Although the causes of ALD are not well established, some studies have revealed that alcohol-induced oxidative stress, hepatotoxicity, and the complex interactions involving alcohol metabolism, liver cells, and multiple cytokines can affect the progression of ALD [26]. The antioxidant and anti-inflammatory effects of eupatilin were examined in several studies [15,17,27,28]. Recently, pharmacokinetic study also performed to demonstrate its potential benefit for diverse applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the causes of ALD are not well established, some studies have revealed that alcohol-induced oxidative stress, hepatotoxicity, and the complex interactions involving alcohol metabolism, liver cells, and multiple cytokines can affect the progression of ALD [26]. The antioxidant and anti-inflammatory effects of eupatilin were examined in several studies [15,17,27,28]. Recently, pharmacokinetic study also performed to demonstrate its potential benefit for diverse applications.…”
Section: Discussionmentioning
confidence: 99%
“…5,7-Dihydroxy-3΄,4΄,6-trimethoxyflavone (eupatilin) is a pharmacologically active flavone extracted from an Artemisia species [ 15 ]. Eupatilin is known to have several pharmacological properties, such as anti-oxidative, anti-apoptosis, and anti-inflammatory [ 16 , 17 ]. Additionally, it exhibits therapeutic effects on gastritis and peptic ulcers associated with different cytokines and neuropeptides that can affect gastrointestinal motility [ 18 ], gastric mucosal damage [ 19 ], cerulein-induced pancreatitis [ 20 ], dextran sulfate sodium-induced colitis [ 21 ], and reflux esophagitis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%